Essays on Economics and Management : Applications of Behavioral Science in Organizations - Houdek, Petr, 1981- (2016)
The thesis consists of four conceptual articles focused on application of theories and findings of behavioral economics and behavioral ethics in the sphere of managerial science (What Comes to a Manager's Mind: Theory of Local Thinking; A Perspective on Consumers 3.0: They Are Not Better Decision-Makers Than Previous Generations; Professional Identity and Dishonest Behavior; Puppet Master: Possible Influence of Parasite Toxoplasma gondii on Managers and Employees). The thesis contains introductory unifying commentary that deals with the replication crisis in management science and then speculates on the possibilities of behavioral organization economics. Introductory commentary contains also a summary of the main ideas presented in the conceptual articles and complementary empirical studies listed in the Appendix.